Optical Fingerprints of Nematicity in Iron-Based Superconductors - Degiorgi, Leonardo (Frontiers in Physics, 2022)
Nematicity, which refers to a phase of broken rotational but preserved translational symmetry, is underlined by the appearance of anisotropic properties and leaves remarkable fingerprints in all measurable physical quantities upon crossing the structural tetragonal-orthorhombic transition at T_s in several iron-based materials. Here, we review part of our own broadband optical investigations, addressing the impact of nematicity on the charge dynamics, as a function of temperature and of tunable applied stress, the latter acting as an external symmetry breaking field. We shall first focus our attention on FeSe, which undergoes a nematic (structural) transition without any subsequent onset of magnetic ordering below T_s. FeSe thus provides an opportunity to study nematicity without the limitations due to the reconstruction of the Fermi surface because of the spin-density-wave collective state in the orthorhombic phase, typical for several other iron-based superconductors. Our data reveal an astonishing anisotropy of the optical response in the mid-infrared-to-visible spectral range, which bears testimony of an important polarization of the underlying electronic structure in agreement with angle-resolved-photoemission-spectroscopy results. Our findings at high energy scales support models for the nematic phase resting on an orbital-ordering mechanism, supplemented by orbital selective band renormalization. The optical results at energies close to the Fermi level furthermore emphasize scenarios relying on scattering by anisotropic spin-fluctuations and shed new light on the origin of nematicity in FeSe. Moreover, the composition at which the associated Weiss temperature of the nematic susceptibility extrapolates to zero is found to be close to optimal doping (i.e., in coincidence with the largest superconducting transition temperature), boosting the debate to what extent nematic fluctuations contribute to the pairing-mechanism and generally affect the electronic structure of iron-based superconductors. The present review then offers a discussion of our optical data on the optimally hole-doped Ba_0.6K_0.4Fe_2As_2. We show that the stress-induced optical anisotropy in the infrared spectral range is reversible upon sweeping the applied stress and occurs only below the superconducting transition temperature. These findings demonstrate that there is a large electronic nematicity at optimal doping which extends right under the superconducting dome.